A companion to the Harlem Renaissance - Sherrard-Johnson, Cherene, 1973- (Chichester, West Sussex, UK ; Malden, MA, USA : Wiley Blackwell, 2015)
'A Companion to the Harlem Renaissance presents a comprehensive collection of original essays that address the literature and culture of the Harlem Renaissance from the end of World War I to the middle of the 1930s'--Provided by publisher.
Includes bibliographical references and index.
Print version record.
Keywords: 1900-1999; Harlem Renaissance; American literature -- African American authors -- History and criticism; African American arts -- New York (State) -- New York -- 20th century; African Americans in popular culture; African Americans in literature; Literature and society -- United States -- History -- 20th century; Harlem (New York, N.Y.) -- Intellectual life -- 20th century; Electronic books